Singapore Management University Report to Stakeholders 2008 - 2009 - Singapore Management University (Institutional Knowledge at Singapore Management University, 2008)
SMU was envisioned as a bold experiment to redefine tertiary education in Singapore. Taking up the gauntlet to bring university education to a new threshold, it challenges itself to become a leading research university known for its innovative pedagogy that produces a different kind of graduate: all-rounded, talented individuals who can think creatively and divergently, filled with business world savvy and strong interpersonal skills yet rooted in social consciousness. The untested ideas of yesterday have become pages after pages of success stories which we continue to celebrate every Commencement in August. Against the backdrop of not only the worst global economic recession in living memory, but also a collapse of business ethics across corporate and business leadership, we pause for a moment to revisit the role of universities. The benefit of hindsight is a validation that SMU has chosen the right track. Our emphasis in providing a values-based education, broad-based curriculum with multidisciplinary learning, industry and global exposure prepares our graduates for challenging times in today’s economic climate. They leave the University with a strong set of skills and knowledge, versatile enough to adapt and survive well in different industries. Character-building, an integral aspect of the SMU education, imparts values of ethics and social responsibility.